A scoping study of sea cucumber as a new therapeutic agent in wounds healing treatment - Azmi, Nurshazwani; Lestari, Widya; Kahzan, Khazlan Afiq; Haris @ Harith, Muhammad Salahuddin; Mazlan, Nurzafirah (2022)
The ocean is a vast resource of natural compounds that give a number of medicinal advantages to the health functions of human beings. Sea cucumbers, also known as gamat, have long been used as alternative medicine in Asian and Middle Eastern countries, especially in treating cuts and burns. Due to their pharmacological benefits, sea cucumbers have been explored for medical use, especially in dermatological formulas for wound healing. The therapeutic effects of sea cucumber, such as their anti-inflammatory,antibacterial, antioxidant, and anti-coagulant properties, due to the existence of biologically active compounds such as saponin, glycoprotein, chondroitin sulphate, phenol, and fatty acids, are imperatively facilitating wound healing management. However, there were still insufficient studies that systematically reviewed the existing literature regarding the evaluation of sea cucumbers as a wound healing treatment. This scoping review will encompass the wound healing potential of sea cucumber for in vivo and clinical studies where the searches were conducted using three main databases, which are PubMed, Science Direct, and Google Scholar, with papers released between 1970 and 2021. Twelve studies met the inclusion criteria in which these studies compromise in vivo and clinical studies that evaluate five different types of wounds, which are excision, incision, ulcer, diabetic, and burn wounds. Findings from in vivo and clinical studies provide consistent evidence through macroscopic and microscopic observation; most of the studies prove that sea cucumber can enhance tissue repair and wound healing through fibroblast proliferation, regulation of inflammatory response, and amplifying the angiogenesis process.